Thermal and biodegradation properties of biopolymer produced from paper mill wastewater - Heng, Su Cin (2019)
Polyhydroxyalkanoate (PHA) is known as a type of biopolyester, which stored within the cells as energy storage materials by various microorganisms. The characterization of polyhydroxyalkanoate produced from papermill wastewater was investigated in this study. The papermill wastewater was treated by activated sludge process and PHA was formed inside the aerobic granules. Subsequently, the chemical structure and thermal properties of PHA synthesized was analysed. The PHA synthesized was proven to be P3(HB-co-HV) which consists of 3-hydroxybutyrate and 3-hydroxyvalerate monomers. Besides, its melting point was determined as 101.57°C and it lost about 30% of its initial weight throughout 8 weeks in biodegradation test. The tested samples exhibited similar melting point and weight loss. Overall, the PHA produced contained good processability and potential to substitute petroleum-based plastics. In this study, different activated sludge weights and aeration rates showed varying results in COD removal efficiency. The COD removal efficiency was increased from 51.91% until 76.31% when the activated sludge weight was increased from 200g to 400g. On the other hand, COD removal efficiency was promoted from 70.69% to 78.91% by increasing aeration rate from 1L/min to 3L/min. Hence, further study was carried out to investigate the effect of aeration rate of activated sludge weight on PHA yield produced from papermill wastewater. The PHA yield was increased from 19.17mg/g to 32.40mg/g as the activated sludge weight was increased from 200g to 400g. Conversely, the PHA yield were 26.40mg/g, 32.40g/mg and 28.90mg/g when the aeration rate was set as 1L/min, 2L/min and 3L/min respectively. Aeration rate showed a positive effect on the COD removal efficiency and MLSS of the sample, which is important in a wastewater treatment system.